Central Asian and Caspian Gas Production and the Constraints on Export - Pirani, S (Oxford Institute for Energy Studies, 2012)
There has been a great deal of discussion about the Central Asian and Caspian region’s potential to produce and export gas, and about projects designed to establish new pipeline routes, e.g. to Europe and South Asia. The discovery of the South Yolotan (Galkynysh) field in Turkmenistan, now confirmed as one of the world’s largest, has renewed interest in the region. But the reality has confounded many expectations. Apart from traditional export routes to Russia and Iran, the only new corridor opened up has been to China. This detailed survey of the region, focussed mainly on the four main gas producers (Turkmenistan, Uzbekistan, Kazakhstan and Azerbaijan), examines why the presence of considerable resources does not necessarily guarantee rapid development. The political and economic background, the upstream conditions and domestic markets are considered, as well as the export trade.